ARDUINO - SMART HOME FIRE SENSOR - Raja Badrul Zaman, Raja Mohd Zahid Hakim (Journal of Computing Technologies and Creative Content, 2019)
Fire outbreak are regularly disasters in Malaysia happen due to the carelessness or weather. Instant fire alerting system is important to make sure the fire outbreak will not spread widely. Arduino - Smart Home Fire Sensor is an automatic fire alerting system which are capable to detect fire, smoke, body movement, and GPS that can provide the location of the incident. Arduino Mega has been used to integrated with all the sensor. The system will be calling for emergency immediately and sending message to alert the fireman and it can recognize the signaling to identify fire ahead of schedule as to initiate various action. This project used GSM module to send the message Via SMS from the Arduino board, then nodeMcu used for getting data to transmit to firebase database. Lastly, this prototype has been successfully developed.